EFEKTIVITAS MANAJEMEN PROGRAM SEKOLAH PENGGERAK (Studi di SMP Negeri 7 Langsa) - Mariono, Mariono; Akrim, Akrim; Siregar, Astri Novia (Hijri, 2024)
The Driving School Program aims and focuses on developing overall student learning achievement by implementing the Pancasila Student Profile. The scope of competencies developed is cognitive (literacy and numeracy) and non-cognitive (character). To achieve this goal, an analysis is needed to measure its effectiveness. Then through the Countenance Stake model evaluation method which focuses on the level of achievement in program implementation by comparing the results of observations with reference criteria and producing recommendation decisions. The subject of this evaluation research was SMP Negeri 7 Langsa which implemented the driving school program intervention in its school. This research uses an evaluative method using data collection techniques through observation, interviews, documentation and questionnaires. The results of the Stake evaluation show that the Antecedent component (input/planning) of the Driving School Program at SMP N 7 Langsa is running effectively which shows the readiness of several elements that influence the success of PSP at SMP N 7 Langsa so that it has systemic managerial implications with mature strategies in achieving goals, in the Transaction (process) component of SMP N 7 Langsa implementing PSP in the four elements of the management process, namely planning, organizing, actuating and controlling and in the Outcome (results) component, achievements have been realized at each of the previous stages of the program both managerially and evaluatively . The results of evaluation research using the Stake Countenance Model can show that the evaluated aspects have met the predetermined objective standards. Detailed and comprehensive program information can be found in each discussion at the antecedent, transactions and outcomes stages, so that it is easier to determine the effectiveness of the managerial implementation and to anticipate corrective actions and recommendations for the next program